Determinants of Access to Finance for SMEs: Evidence of Sayaboury Province, Lao PDR - SENGDALA, Chansamone; HER , Pheng (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
Lao PDR is one of the least developed countries which an average income of less than 1.90/day therefore access to finance or formal and informal credits is very important for lifestyle and business operation. For evidence of Sayaboury district and province, it is a province that share border with Thailand, so access to finance to support manufacturing and services is necessary. Based on literature reviews, the researcher tries to survey the Small and Medium Enterprises (SMEs) which registered with the department of industry and commerce of Sayaboury district, a total of 1,492 enterprises. Thus, I used the Taro Yamane (1975) method to random and equal to 136 sampling or questionnaires and implied with a binary logistic regression model to estimate the probabilities of SMEs to access to finance. The results found that there are only four factors that determinants of the SMEs’ access to finance for evidence of Sayaboury district and province at 1% statistical significance level, including collateral, business sector, business plan and business information. While as the age of business is significant at the statistically 10% level. The study reveals that lenders or creditors discriminate those factors which the business or entrepreneur that has collateral are 23.85 times more likely affected to access finance than other do not have and the entrepreneurs who have a business plan can access finance more than the others do not have with 6.72 times. Furthermore, the manufacturing sector is able to access to finance than the SMEs who operator services 0.32 times. In addition, the entrepreneurs who can access the information of lenders have the probability to have access to finance are 0.14 times more likely than others at 1% statistical level. But the age of business significant effect on the SMEs’ access to finance at 10% statistically level, meaning that if a one-year increase in the age of business is more likely increase access to finance or loan by 4.6%. In this paper, the researcher does not compare the access to formal and informal finance and the structure of SMEs, therefore further researchers should consider the structure of SMEs promotion and support in Laos.